IMPLEMENTATION OF CREATIVE ECONOMY MODELS IN CULTURAL HERITAGE MANAGEMENT IN KARAKALPAKSTAN - Dlimova Zulfiya Sırģabay qızı (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article extensively analyzes the scientific foundations and practical mechanisms for implementing creative economic models in improving the cultural heritage management system in the Republic of Karakalpakstan. The purpose of the research is to develop a strategy for transforming the historical, archaeological, and ethnocultural potential of the region into a factor of sustainable economic development.